Optimising Hepatitis C care in an urban Aboriginal and Torres Strait Islander primary health care clinic - Prabha Lakhan; Deborah Askew; Noel Hayman; Leigh‐anne Pokino; Cheryl Sendall; Paul J. Clark (Elsevier, 2019)
Abstract Objective: Describe the sociodemographic and clinical characteristics of patients with Hepatitis C Virus (HCV) attending an urban Indigenous primary health clinic (IPHC) in Brisbane, Australia. Methods: A retrospective chart review of sociodemographic characteristics, presence of liver disease and treatments, lifestyle behaviours and comorbidities in patients with a HCV infection was conducted between October 2015 and March 2016. Results: One hundred and thirteen patients with confirmed HCV infection were aged between seven and 63 years; 66% were male, and 84% were Indigenous. Sixty‐nine per cent had been incarcerated; 41% had experienced conflict or domestic violence; 47% were injecting drugs; 72% had depression; and 61% had anxiety. Cirrhosis was present in 7/95 patients with adequate data and associated with age (p=0.02). Eleven patients had commenced direct acting antiviral (DAA) therapy in the 18 months that it had been available. Conclusions: The study highlights the opportunities for enhancing treatment of patients with HCV infection. Opportunities to improve treatment rates in an Indigenous primary healthcare include optimising diagnostic pathways, improving patient engagement, and general practitioner and peer worker participation. Implications for public health: HCV poses a serious threat to public health in Australia and IPHCs are key sites to addressing this for Indigenous people. Optimising care of patients with HCV attending IPHC requires recognition of the complex health needs and social context, to reduce the incidence and consequences of HCV infection.